2010
DOI: 10.1186/1472-684x-9-22
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of a hand-held fan for breathlessness: a randomised phase II trial

Abstract: BackgroundBreathlessness is common and distressing in advanced disease. This phase II study aimed to determine the use and acceptance of a hand-held fan (HHF) to relieve breathlessness, to test the effectiveness of the HHF and to evaluate the recruitment into the study.MethodsRCT embedded within a longitudinal study testing a HHF over time compared to a wristband. Patients were included in the longitudinal study when suffering from breathlessness due to advanced cancer or COPD III/IV and could opt in the RCT. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
81
0
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(87 citation statements)
references
References 13 publications
3
81
0
3
Order By: Relevance
“…Participants described fan-related benefits in terms of a quicker recovery from breathlessness rather than as a reduction in breathlessness severity, which has been the focus of recent trials [15][16][17][18]. With notable exceptions, patients used the fan when resting after physical activity rather than prior to or during activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Participants described fan-related benefits in terms of a quicker recovery from breathlessness rather than as a reduction in breathlessness severity, which has been the focus of recent trials [15][16][17][18]. With notable exceptions, patients used the fan when resting after physical activity rather than prior to or during activity.…”
Section: Discussionmentioning
confidence: 99%
“…Two randomised controlled trials (RCTs) found a statistically significant reduction in breathlessness severity from the fan, both of which focused on short-term administration (single use or during 1 week) [15,16]. Two further phase II mixed-methods RCTs were not designed to test efficacy but yielded qualitative data suggesting that the fan reduced recovery time after activity and conferred a feeling of control for some patients [17,18]. Two other qualitative analyses suggest that patient characteristics and nuances in the way fans are used may determine the degree and type of benefit experienced [19,20].…”
Section: Introductionmentioning
confidence: 99%
“…Patients who were near death and at risk for dyspnea remained comfortable without oxygen [69]. A fan directed at the patient’s face may provide relief [70], although use in the ICU may be limited by bioengineering restrictions.…”
Section: What Are Current Strategies For Managing Symptoms During Crimentioning
confidence: 99%
“…[7], psychomotorische Hemmung oder Aktiviertheit [8], Schlafstörungen [9] und Appetitverlust [10]. Aus der Anzahl der Symptome ergibt sich dann die Einstufung als leicht (4-5 Symptome), mittelgradig (6-7 Symptome) oder schwer (> 7 Symptome), wobei mindestens 2 Hauptsymptome gegeben sein müssen.…”
Section: Definitionunclassified